The Role of Management in the Internationalization Process of a Firm - Erdal Yalcin; Davide Sala (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In this paper we are able to analyze firms' entry decision into the export market. In contrast to previous studies it is possible to control for the effects of management characteristics and human capital variables, besides commonly used firm characteristics. We first motivate our empirical strategy by presenting a theoretical partial equilibrium model which accounts for management characteristics as an input factor. Applying an empirical strategy suggested by Chamberlain (1980) we are able to affirm the robustness of firm productivity and fixed costs as explaining variables for export decisions. Unobserved heterogeneity turns out to be systematically related to management characteristics, in particular management knowhow. By reducing the sample only to firms which enter the export market during the considered period, the type of management promotion (internal promotion opposed to e.g. external promotion) is identified to increase the likeliness of exporting.
Keywords: F23; L23; L25; 330; Export Decision; Internationalization; Management; Productivity